2007
DOI: 10.1210/en.2006-0848
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin A Is an Endocrine Stimulator of Bone Mass and Strength

Abstract: Gonadal function plays a major role in bone homeostasis. It is widely held that the skeletal consequences of hypogonadism are solely due to a loss of sex steroids; however, increases in bone turnover begin during perimenopause before decreases in serum estradiol levels. These data and our demonstration that inhibins acutely regulate bone cell differentiation in vitro led us to test whether inhibin A (InhA) regulates bone mass in vivo. Using a transgenic model of inducible human InhA expression, InhA increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
93
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 91 publications
10
93
0
1
Order By: Relevance
“…(31) This is also consistent with the observation that inhibin-A, which also blocks activin-A, is a stimulator of bone mass and strength. (29) In addition to investigating the effects of activin-A and ActRIIA.muFc on osteoblastogenesis, we also examined their effects on osteoclast formation. We found that activin-A did not significantly alter osteoclast number or activity in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(31) This is also consistent with the observation that inhibin-A, which also blocks activin-A, is a stimulator of bone mass and strength. (29) In addition to investigating the effects of activin-A and ActRIIA.muFc on osteoblastogenesis, we also examined their effects on osteoclast formation. We found that activin-A did not significantly alter osteoclast number or activity in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…(24)(25)(26)(27) In vivo, direct administration of activin-A increases bone mineral density (BMD), (28) whereas overexpression of inhibin-A, which blocks activin-A and other TGF-b family members, increases bone mass. (29,30) We have demonstrated recently that activin-A signaling can be blocked in vivo with a soluble ActRIIA.muFc fusion protein, leading to increased bone mass and strength. (31) Levels of activin-A have been shown to be increased in the sera of patients with breast and prostate cancer and to be increased further in the presence of metastases.…”
Section: J Jbmrmentioning
confidence: 99%
“…32 Thawed specimens were soaked in saline for 1 hour before testing to ensure hydration and then tested at room temperature using a servohydraulic-testing machine MTS 858 Bionex test systems load frame (MTS, Eden Prairie, MN) with computer control, data logging, and calculations of load to failure using TestWorks version 4.0 (MTS). Bones were placed with their anterior side down on two horizontal supports spaced 7 mm apart; the central loading point contacted the posterior surface of the diaphysis at the midpoint of the bone length.…”
Section: Whole Femur Mechanical Testingmentioning
confidence: 99%
“…Loaddisplacement data were recorded at 100 Hz (TestWorks 4.0, MTS), and test curves were analyzed to determine measures of whole-bone strength, primarily peak load and stiffness as we have described. 32 Load to failure was recorded as the load after a 2% drop from peak load.…”
Section: Whole Femur Mechanical Testingmentioning
confidence: 99%
“…24 Moreover, mFEA of excised bones is non-destructive allowing for subsequent histological analysis. Although a number of studies involving rodents have used mFEA to determine the effect of drug treatment on bone strength, [25][26][27][28][29][30] there is little evidence in the literature establishing that mFEA can accurately predict the mechanical properties of rodent bone, and especially murine bones. Of the few studies comparing FEA predictions to experimental measurements of strength in rodent tissues, long bones were tested with limited examination of material definitions.…”
Section: Introductionmentioning
confidence: 99%